Turkiye's Water Security Policy: Energy, Agriculture, and Transboundary Issues - Kibaroğlu, Ayşegül (SETA Foundation, 2022)
Water security refers to the availability of adequate quantities and qualities of water for societal needs and resilient ecosystems in the context of current conditions and future global change. Achieving water security is directly linked to food and energy security, protecting and preserving eco systems, and addressing key vulnerabilities and risks from climate change. Good water governance –including transboundary cooperation– is a crit ical feature of any effort to achieve water security. Yet the concept of water security remains abstract and broad. In an attempt to make the concept of water security-relevant in practice, this paper delineates Türkiye’s water se curity policy and practices through institutional and cross-sectoral (energy and food) analysis. Specific attention is paid to Türkiye’s transboundary water security policies.
Keywords: Turkiye; Water policy institutions; Water and agriculture; Transboundary water security; Çevre Çalışmaları; Su Kaynakları